The nitrite content in domestic and foreign cooked sausages from the Serbian market. (September 2019) - Djordjevic, V; Baltic, T; Parunovic, N; Simunovic, S; Tomasevic, I; Velebit, B; Ciric, J
Abstract: The nitrite content (expressed as NaNO2 ) was measured in 236 samples of different types of domestic and foreign cooked sausages from the Serbian market, according to standard ISO procedure. The highest content of nitrite (expressed as NaNO2 ) was found in fine comminuted cooked sausages from foreign producers. Similarly, the coarse comminuted cooked sausages from foreign producers contained higher nitrite compared to domestically produced cooked sausages. According to National and EU Regulations, the maximum allowed nitrate content (expressed as NaNO2 ) is 150 mg/kg. All tested cooked sausages had nitrite levels below the regulatory limits set by National Regulation and Regulation (EC) No. 601/2014, but the highest nitrite contents were found in cooked sausages from foreign producers.